2017
DOI: 10.4102/sajip.v43i0.1436
|View full text |Cite
|
Sign up to set email alerts
|

Leadership styles: The role of cultural intelligence

Abstract: Orientation: Within both the South African context and abroad, leaders are increasingly being required to engage with staff members whose cultures differ from their own. As the attractiveness of different leadership styles varies in line with staff member cultural preferences, the challenge leaders face is that their behaviours may no longer be apposite. To this end, it is mostly unknown whether those leaders who are deemed culturally intelligent behave in a specific manner, that is, display the empowering and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 104 publications
(118 reference statements)
1
31
0
Order By: Relevance
“…According to Clark et al (2009), leadership is "the manner and approach for providing direction, implementing plans, and motivating people" (p. 1). Importantly, transformational, transactional, and laissez-faire are reported as some of the most widely practiced leadership styles for galvanizing employee behaviors and fostering positive outcomes (Afifah & Daud, 2018;Anderson & Sun, 2017;Chang et al, 2019;Chiniara & Bentein, 2018;Cummings et al, 2010;Han et al, 2016;Huertas-Valdivia et al, 2019;Miao et al, 2018;Skakon et al, 2010;Solomon & Steyn, 2017). Burns (1978) has defined transformational leaders as the one capable of nurturing followers up from their petty preoccupations and rally them around a common purpose to achieve things never thought possible.…”
Section: Leadershipmentioning
confidence: 99%
“…According to Clark et al (2009), leadership is "the manner and approach for providing direction, implementing plans, and motivating people" (p. 1). Importantly, transformational, transactional, and laissez-faire are reported as some of the most widely practiced leadership styles for galvanizing employee behaviors and fostering positive outcomes (Afifah & Daud, 2018;Anderson & Sun, 2017;Chang et al, 2019;Chiniara & Bentein, 2018;Cummings et al, 2010;Han et al, 2016;Huertas-Valdivia et al, 2019;Miao et al, 2018;Skakon et al, 2010;Solomon & Steyn, 2017). Burns (1978) has defined transformational leaders as the one capable of nurturing followers up from their petty preoccupations and rally them around a common purpose to achieve things never thought possible.…”
Section: Leadershipmentioning
confidence: 99%
“…However, Grand et al (2013) and Collins et al (2016) did not find that CQ has predictive power for these objective results. CQ can also be positively connected to interrelationship variables, such as group acceptance for newcomers (Joardar, Kostova, & Ravlinet, 2007) and different leadership styles (Ramsey, Rutti, Lorenz, Barakat, & Sant'anna, 2017;Solomon & Steyn, 2017).…”
Section: Chen and Song 2012)mentioning
confidence: 99%
“…Overall, CQ has been linked to transformational leadership, which emphasizes offering followers a vision and inspiring them by acting as role models (Ramsey et al, 2017), while Solomon and Steyn (2017) found that leaders' metacognitive CQ and motivational CQ are better predictors for empowering leadership (i.e., focus on assigning authority and responsibilities to followers) than for directive leadership (i.e., emphasizing precise goals and instructions). Young, Haffejee, and Corsun (2017) found that overall CQ and all dimensions of CQ, with the exception of cognitive CQ, are negatively related to ethnocentrism.…”
Section: Chen and Song 2012)mentioning
confidence: 99%
“…Cultural intelligence is defined as the ability of effective adaptation in different cultural environments (Ang, Van Dyne, & Rockstuhl, 2015;Earley, 2002) the ability to adapt to others (Ng & Earley, 2006) and to various cultural situations (Ang, Van Dyne, & Koh, 2006), i.e., cultural empathy (Ridley & Lingle, 1996) and is motivated by the real practice of globalization both in the workplace (Earley & Ang, 2003) and in the society. Thus, a high level of cultural intelligence allows the adaptation and modeling of behavior, before the contact with people from different cultural areas (Solomon & Steyn, 2017). Cultural intelligence is a set of capabilities and skills that allow us to interpret behaviors and situations that are unfamiliar, as well as, identify behaviors that are universal to all mankind, behaviors that are cultural and behaviors that are idiosyncratic to one particular individual in a specific situation (Van Dyne, Ang, & Livermore, 2010).…”
Section: Cultural Intelligence and Intercultural Contactmentioning
confidence: 99%